Nodulation Behaviour Of Acacia Mangium Wikd.In Response TO Rhizobium Inoculation - Dhaneshkumar P (Department of Tree Physiology and Breeding, College of Forestry, 1998)
An investigation was carried out during April 1996 to December 1997 at the College of Forestry, Kerala Agricultural University, Vellanikkara to study the nodulation characteristics of Acacia mangium Willd. plantation and to isolate and compare the efficiency of rhizobia from different agroclimatic regions of Kerala. The efficiency of these rhizobial isolates under varying conditions of soil fertility and acidity were also evaluated. Survey conducted throughout the state showed rhizobial association and nodulation in all mangium plantations. The soil of these plantations were acidic with pH values ranging from 4.9 to 6.2. Experiments conducted to study the rhizobial characteristics indicated that, the fast growers (Rhizobium spp.) as well as the slow growers tBradyrhizobium spp.) are involved in nodulation of A. mangium in Kerala. The efficiencies of different rhizobial isolates were studied in polypots using sterilized and unsterilized soil - sand mixture. Two other polypot experiments were conducted to study the response of the rhizboial isolates to liming and Nand P application. The experiments were laid out in C.R.D with three replications. Seedlings raised in unsterilized soil performed better as compared to seedlings in sterilized soil. However, the response to inoculation was more prominent in sterilized soil. In sterilized soil, seedlings inoculated with Rhizobium isolates from mangium ;MRh-3 (Mananthavadi), MRh- 2(Perambra), MRh-13 (Trivandrum), MRh-6 (Vellanikkara) and MRh-lO (Mavelikkara) and commercial mangium culture (" Agroforester - Group A") showed superiority in nodulation and growth characteristics while the isolates from A. auriculijonnis and commercial culture of A. auriculijonnis, ("Agroforester - Group C") were not much effective.